Árokháty Béla – az orgonatervező - FEKETE, Károly (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
Béla Árokháty, the Organ Builder. This study present Béla Árokháty’s biography, who was not only a musician but also a minister leading and inspiriting his flock. It also high-lights that the people rebelled against him because of the novelties he adopted. Béla Árokháty was convinced that the Protestant musical treas-ure must become accessible to all. In several of his writings, he accepted the rules regarding religious church music and instrumentation, but from the beginning of his religious musicological activity and, until the last, his aim was to favour the widespread adoption of church music in the Reformed Protestant service. Very few of his contemporaries recog-nized his personality and mission, however he was the one who launched the reform of the musical culture in the Protestant communities of the 20ᵗʰ century. Béla Árokháty’s exceptional initiatives and his achievements have largely contributed to raising Hungarian Reformed religious music to European standards.